Two new siderophores produced by Pseudomonas sp. NCIMB 10586: The anti-oomycete non-ribosomal peptide synthetase-dependent mupirochelin and the NRPS-independent triabactin - Grosse, Camille; Brandt, Nathalie; Van Antwerpen, Pierre; Wintjens, René; Matthijs, Sandra (Frontiers in Microbiology, 2023)
Globisporangium ultimum is an oomycetal pathogen causing damping-off on over 300 different plant hosts. Currently, as for many phytopathogens, its control relies in the use of chemicals with negative impact on health and ecosystems. Therefore, many biocontrol strategies are under investigation to reduce the use of fungicides. In this study, the soil bacterium Pseudomonas sp. NCIMB 10586 demonstrates a strong iron-repressed in vitro antagonism against G. ultimum MUCL 38045. This antagonism does not depend on the secretion of the broad-range antibiotic mupirocin or the siderophore pyoverdine by the bacterial strain. The inhibitor molecule was identified as a novel non-ribosomal peptide synthetase (NRPS) siderophore named mupirochelin. Its putative structure bears similarities to other siderophores and bioactive compounds. The transcription of its gene cluster is affected by the biosynthesis of pyoverdine, the major known siderophore of the strain. Besides mupirochelin, we observed the production of a third and novel NRPS-independent siderophore (NIS), here termed triabactin. The iron-responsive transcriptional repression of the two newly identified siderophore gene clusters corroborates their role as iron scavengers. However, their respective contributions to the strain fitness are dissimilar. Bacterial growth in iron-deprived conditions is greatly supported by pyoverdine production and, to a lesser extent, by triabactin. On the contrary, mupirochelin does not contribute to the strain fitness under the studied conditions. Altogether, we have demonstrated here that besides pyoverdine, Pseudomonas sp. NCIMB 10586 produces two newly identified siderophores, namely mupirochelin, a weak siderophore with strong antagonism activity against G. ultimum, and the potent siderophore triabactin.